Analysing the role of National Women Entrepreneurship Council in promoting entrepreneurial culture in Mauritius - Roopchund, Randhir (Technium Social Sciences Journal, 2020)
The current study is presented as a Case study to analyse the role of the National Women Entrepreneurship Council in promoting and developing an effective entrepreneurial culture in Mauritius. The NWEC is a parastatal body working under the aegis of the Ministry of Gender, Child Development and Family Welfare. The case study seeks to provide an insight on the overall role and functions and challenges faced by the organisation to promote female entrepreneurship. The research approach is qualitative using content analysis and multi-case methods with interviews to analyse the effectiveness of the institution. The case study will be of great significance to different stakeholders including the Ministry of Gender, the women entrepreneurs and other NGOs which are actively participating to reduce gender inequality